Rasionalitas Pengadilan Agama Melegitimasi Pernikahan Dini Di Desa Gemaharjo - Ardiyono, Fahrul; Handoyo, Pambudi (Paradigma, 2024)
Early marriage is a phenomenon that still occurs in Indonesia. In early marriage, there is one condition that is not fulfilled in state regulations, namely the age of the perpetrator or bride and groom. In marriage law, the age limit for a person to marry is 19 years. Some of the reasons for early marriage in Indonesia are arranged marriages, economic needs, and promiscuity. Early marriage can be legally recognized by the state by obtaining legitimacy approval from a religious court as a condition for KUA registration. Therefore, the formulation of this research problem is the rationality of religious courts legitimizing early marriage in Gemaharjo village. The theory used as an analytical tool in this research is Max Weber's bureaucratic theory. The method used is a qualitative research method of descriptive analysis by conducting field observations and conducting interviews to obtain data according to research needs. The results of this research are that the religious court as the authority holds the rules in accordance with applicable law, granting legitimacy to early marriage is given with strong considerations. According to Max Weber, the decision to legitimize early marriage by the Religious Court is a form of rational legal authority possessed by the Religious Court. Bureaucracy can suppress early marriage, but public awareness is very important to provide understanding to the younger generation about the dangers of early marriage